Diplomasi Kebudayaan China dalam Hubungan Dagang dengan Uni Emirat Arab - Ellen Monica Audrey Suharyanto; Christy Damayanti; Untari Narulita Madyar Dewi (UIN ALAUDDIN MAKASSAR, 2023)
Since the Tang Dynasty in 618-907, China has begun to use soft power diplomacy to influence Middle Eastern countries by spreading their products. Since then, China has begun to prioritize their soft power diplomacy to establish relations with other countries and based on the culture they hold quite closely. China and the United Arab Emirates (UAE) have established bilateral cooperation since 1971, and the two countries' political, economic and commercial ties have developed since then. With different cultural backgrounds between the two countries, China uses culture as a tool to explore with the UAE in order to improve trade relations between the two countries. The author sought to explain how China uses culture as an entry point to penetrate trade cooperation with the UAE with the concept of cultural diplomacy and trade diplomacy. This form of research uses qualitative research methodologies as well as by using primary and secondary data sources. The purpose of this study was to find out China's strategy in using culture as an entry point in the field of trade using library research methodology. From the analysis, it can be concluded that China's cultural diplomacy towards the UAE with cultural strategies in improving trade relations between the two countries, marked by the signing of cooperation and other conferences.